Oogenesis in the Bemisia tabaci MEAM1 species complex. (April 2016) - Guo, Jian-Yang; Wan, Fang-Hao; Ye, Gong-Yin
Highlights: Oogenesis of B . tabaci MEAM1 is first examined among 34 whitefly species complex in the world. Telotrophic ovarioles are observed in MEAM1. Each ovariole has two well defined regions: tropharium and vitellarium. Development of single oocyte in vitellarium has four phases: early oocyte formation, previtellogenesis, vitellogenesis and choriogenesis. Oocyte could transport yolk and bacteria through nutritional tunnel and space of follicle cell. Abstract: The whitefly Bemisia tabaci MEAM1 species complex has invaded several parts of the world in the past 30 years and replaced native whitefly populations in the invaded regions, including certain areas of China. One of the possible reasons for the invasion is that MEAM1 whiteflies are more fecund than native species. However, the factors that affect the reproduction of the B. tabaci cryptic species are not clearly known. The regulation of oogenesis is thought to be one of the essential processes for egg formation and ovary development and could affect its population dynamics. In this study, the ovariole structure and oogenesis of the MEAM1 species complex was examined using light and transmission electron microscopy. Telotrophic ovarioles were observed in the MEAM1 species complex. Each ovariole had two well defined regions: the tropharium and the vitellarium. The tropharium always had more than ten trophocytes. The development of a single oocyte in the vitellarium has four phases: oocyte formation, previtellogenesis, vitellogenesis and choriogenesis. Two arrested oocytes, follicular cells and uncompleted oocytes were separated from the tropharium by microtubule and microfilaments. Early previtellogenesis oocytes absorbed nutrients and endosymbiont bacteria through a nutritive cord. However, the vitellogenesis of oocytes transmitted Vg through both the nutritive cord and the space between follicular cells. Each mature oocyte with deposited yolk proteins had only one bacteriocyte and was surrounded by a single layer of follicular cells. The oogenesis in the B . tabaci MEAM1 species complex concluded with the differentiation of oocytes, the transport of yolk and endosymbionts as well as the development and maturation of oocytes. This result provides important information that further defines the regulation of oogenesis in the B. tabaci complex.